NCFET-Based 6-T SRAM: Yield Estimation Based on Variation-Aware Sensitivity - Yuri Hong (IEEE Journal of the Electron Devices Society, 2020)
The key feature of NCFET (negative capacitance field effect transistor) is its sub-threshold slope (SS) <; 60 mV/decade at 300 K. In this work, the n-type NCFET (i.e., pull-down (PD) and passgate (PG) transistor in six-transistor (6T) SRAM bit-cell) has SS of 53.92 mV/decade, and the p-type NCFET (i.e., pull-up (PU) transistor in the 6T SRAM bit-cell) has SS of 58.96 mV/decade. In the NCFET-based SRAM cell (vs. conventional SRAM cell with conventional planar bulk MOSFETs), its read (hold)-stability and write-ability are evaluated by the metric of read static noise margin (SNM) and write-ability current (Iw), respectively. Then, under process-induced random variation, sensitivities of SNM and Iw are extracted. Finally, the yield of NCFET-based SRAM array (vs. conventional SRAM array) is quantitatively estimated using the cell-sigma.